Synthesis of B/P/N Containing Flame-Retardant Additives and UV Curable Hybrid Coating Applications - KAHRAMAN, MEMET VEZİR (WILEY, 2017)
The aim of this study is to synthesize flame-retardant additive by using B/P/N and to investigate this additive's performance in the ultraviolet (UV) curable system. Therefore, in the first stage, borate ester (triethanolamine borate, TEAB) was synthesized by the reaction of boric acid and triethanolamine. In the second stage, phosphate salt of borate ester (triethanolamine borate polyphosphoric acid, TEAB-PPA) was synthesized by the reaction of borate ester (TEAB), which synthesized in the first stage and PPA. Thermal stability and flammability of the samples were evaluated by thermal gravimetric analysis, differential scanning calorimetry, and limiting oxygen index. The samples were characterized with the following analyses: Fourier transform infrared, nuclear magnetic resonance, UV transmittance, gel content, water absorption capacity, and stress-strain test. Hydrophilicity of the samples was determined by the contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy-energy dispersive spectrometer mapping. The obtained results prove that boron, nitrogen, and phosphorus increased the flame retardancy property of the synthesized additive and suggest desired flame retardancy using various resins and different ratio of additives.
Keywords: Borate esters; Flame retardance; Morphology; Thermal properties; UV curable; COMPOSITES; POLYMERS; EPOXY; RESIN